Determinants of Financial Inclusion in Selected ASEAN Countries: The Role of Technological Infrastructure and Regulatory Quality - Risvi, Afrinise Nasywa Andita; Rahmawati, Farida (Electronic Journal of Education, Social Economics and Technology, 2026)
This study examines the influence of technological infrastructure and regulatory quality on financial inclusion across six middle-income ASEAN economies over the 2011-2024 period. A Fixed Effects estimator with Driscoll-Kraay corrected standard errors is employed to address cross-sectional dependence and non-constant error variance. Both financial inclusion and technological infrastructure are operationalized as PCA-derived composite indices, while the Regulatory Quality Index serves as the measure for institutional quality. Empirical results indicate that regulatory quality exerts a positive and statistically significant effect on financial inclusion, whereas technological infrastructure yields no significant impact. With respect to the control variables, GDP per capita and urban population share positively and significantly shape financial inclusion outcomes, while inflation exerts a negative and significant effect. Overall, these findings suggest that institutional quality, economic capacity, and structural conditions are more consistent drivers of financial inclusion than digital infrastructure availability alone. The findings further indicate that the contribution of technological development is contingent upon supportive regulatory frameworks and stable macroeconomic conditions. Accordingly, policies aimed at expanding financial inclusion should integrate digital infrastructure development with institutional strengthening, macroeconomic stability, and efforts to address structural disparities in access.